RITUAL RATIF SAMAN MASYARAKAT DESA RESUN KECAMATAN LINGGA UTARA KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Suni Hartini; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Ratif Saman ritual is the tradition of the village net (village), the people of Resun Village, is a traditional ritual that is carried out to clean the village from disturbances of spirits and bad people who intend to disturb the village. The purpose of this study is (1) To find out a brief history Ratif Ritual Saman Community Resun Village North Lingga District Lingga Regency Riau Islands Province. (2) To find out the process of the Saman Ratif Ritual of Resun Village, North Lingga District, Riau Islands Regency. (3) To find out the changes that occurred in the Ratif Saman Ritual in Resun Village, North Lingga District, Lingga Regency, Riau Islands Province. The method used in this study is a qualitative research method. Qualitative method is a method that does not use numbers in data collection and in providing interpretation of the results. The results of the general research that the authors wrote ratif saman rituals in the resun village communities are carried out depending on the condition of how many calamities, but at this time it is rare to do this ritual.Key Words: Ratif Saman, Tradition, Resun Village